1882 Md. Laws 656, §2 - (:unkn) unknown (My University, 1882)
Ch. 424 §2: Prohibited the sale of any firearm or other deadly weapon to minors under the age of twenty-one. Violators fined not less than fifty, but no more than two hundred dollars with costs. Failure to pay fine punished by imprisonment the until the fine is paid, or imprisonment of sixty days max, whichever shall occur first.
Keywords: TRANSFER - MINORS